Reactive Strength Ability Is Associated with Late-Phase Sprint Acceleration and Ground Contact Time in Field Sport Athletes - Eamonn P. Flanagan; Thomas M. Comyns; Andrew J. Harrison; Claire J. Brady (Applied Sciences)
This study investigated the relationship between reactive strength and sprint acceleration performance in elite under-21 hurling athletes. Reactive strength was assessed using the 10/5 Repeated Jump Test (RJT), while sprint performance was measured over 30 m with split times at 5, 10, 20, and 30 m. Twenty-four male players participated in the study. The results revealed large, significant correlations between reactive strength index (RSI) and sprint times in the 5–10 m, 10–20 m, and 20–30 m splits but not in the initial 0–5 m phase. Further analysis showed that athletes with higher RSI scores exhibited significantly shorter ground contact times (CTSPRINT) and superior sprint performance in the 20–30 m segment without compromising step length. These findings suggest that reactive strength plays a crucial role in mid-to-late-phase acceleration, likely due to the ability to produce force rapidly during short ground contact durations. The study also identified a significant, negative correlation between RSI and CTSPRINT, indicating a possible mechanical link. These results support the inclusion of reactive strength development in training programs aiming to enhance sprint performance, especially in field sports requiring repeated high-intensity sprints.